THE EFFECTS OF TEACHING WORD ROOTS ON THE LONG TERM RETENTION OF ENGLISH VOCABULARY - Kenan Akarslan; Hasan Bedir (Ömer Gökhan Ulum, 2019)
Vocabulary learning experience seems to be the most time consuming aspect of language learning. Learners exert considerable energy on words trying to memorize isolate words and sets of exam words which are, in most cases, bound to be forgotten. There are various learning strategies adopted by learners of English to memorize and retain words. Dissecting words into word parts is among these although there are few studies dwelling on the benefits of teaching word roots. Those few studies highlight the effectiveness of teaching and learning vocabulary through Latin and Greek roots. However, they lack any answers as to how much this strategy works in terms of retention in the long run. The aim of this study is to show the impact of teaching word roots both on learners' attitudes and the long term retention of newly learnt lexical items. A quantitatively supported descriptive study was administered throughout the study.